The Effects of Corn Cobs in Feed - Mierliţă, Daniel; Sălăjan, Gheorghe; Georgescu, Bogdan; Odagiu, Antonia (Acta Agraria Debreceniensis, 2001)
This study is part of a larger research work that aims to establish the usefulness of corn cobs, a low cost dietary resource, in the growth of ruminants. Corn cobs are found in large amounts in our country (8.2 mil. tons/year). Increasing the quantity of corn cobs to 50% of the diet in lambs resulted in a decrease by 14.57% in the concentrate intake that is needed to obtain one-kg weight increase. In addition, the diet costs were reduced by 16.33% (Mierliţă, 1999). Increasing the quantity of corn cobs to 20-50% of the diet also resulted in multiplication of bacteria from genus Ruminococcus, that are known to represent about 70-80% of the bacteria population in the rumen. In addition, an increased multiplication rate of large protozoas (i.e. Epidinium, Isotrichia, Diplodinium etc) was observed. This explains the high conversion rate of piruvic acid, a carbohydrate fermentation product, into acetic acid, whereas conversion of piruvic acid into propionic acid decreases. In addition, feed intake and the quantity of digested and absorbed fibers increased by 8.46% and 35.09%, respectively. Thus, a reduction in dietary concentrates needed as nutrient supplies was achieved.